2001
DOI: 10.1093/jn/131.8.2184
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Retinol, α-Tocopherol and the Carotenoids Are Influenced by Diet, Race and Obesity in a Sample of Healthy Adolescents

Abstract: An important part of understanding the functions of vitamin A, vitamin E and the carotenoids in nutritional status assessment, health promotion and disease prevention is knowledge of factors that influence their distribution in human tissues. Our objective was to examine serum concentrations of these nutrients and compounds in a sample of 285 healthy participants, 12-17 y old, from three U. S. cities. Pearson correlations between diet measured with a food frequency questionnaire and serum nutrient concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
97
6
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 43 publications
23
97
6
4
Order By: Relevance
“…The modest strength of the correlation coefficients observed is in the same range to those described in previous papers (Hercberg et al, 1994;Albanes et al, 1997;Neuhouser et al, 2001;Wallstrom et al, 2001). In the present study, alcohol consumers had significantly lower serum concentrations of b-carotene but higher concentrations of selenium than nonconsumers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The modest strength of the correlation coefficients observed is in the same range to those described in previous papers (Hercberg et al, 1994;Albanes et al, 1997;Neuhouser et al, 2001;Wallstrom et al, 2001). In the present study, alcohol consumers had significantly lower serum concentrations of b-carotene but higher concentrations of selenium than nonconsumers.…”
Section: Discussionsupporting
confidence: 90%
“…A second explanation could be that the estimates of b-carotene and fibre intakes among obese individuals fail to detect a lower consumption of foods that would increase serum b-carotene concentrations. Specific studies have found an inverse association between serum a-tocopherol and BMI among adults or adolescents (Gascon-Vila et al, 1997;Rock et al, 1999;Neuhouser et al, 2001;White et al, 2001). The basis for lower serum concentrations of nutrients in obese people compared with nonobese people remains speculative, but it has been suggested that dietary differences and variability in body compartmental sizes are likely explanations (Strauss, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The significant increase in plasma retinol concentration with age in boys and girls has also been reported in national samples of young people living in the USA (Lewis et al, 1990;Ballew et al, 2001;Neuhoser et al, 2001). This increase probably reflects larger liver vitamin A stores that reflect normal physiological changes with growth and does not necessarily indicate better vitamin A status with ageing.…”
Section: Discussionsupporting
confidence: 53%
“…We found an inverse association between energy intake and serum retinol and -tocopherol concentrations. This is in agreement with some previous studies [45][46][47], but others have shown positive or no relation of energy intake to blood -tocopherol or retinol levels [14,47,48].…”
Section: Discussionsupporting
confidence: 93%